Numerical Study of InGaN based Photovoltaic by SCAPs Simulation. (August 2015) - Boudaoud, L.; Khelifi, S.; Mostefaoui, M.; Rouabhia, A.K.; Sahouane, N.
Abstract: The necessity to find new forms of renewable energy is very important and urgent nowadays. The renewable sources of energy derived from the sun are one of the promising options. The photovoltaic cells as one of renewable energy sources have been largely studied in order to obtain cheap, efficient and secure PV cells. The conversion efficiency is the most important property in the PV domain. Indium gallium nitride (InGaN) alloys offer great potential for high-efﬁciency photovoltaics. We present numerical simulations of GaN/InGaN heterojunction solar cells by SCAPs simulation. The calculation of characteristic parameters: short-circuit current density, open-circuit voltage, and conversion efficiency. So, these simulations study the effect of indium content and thickness in these parameters. While the maximum efﬁciency of a p-n GaN/InGaN heterojunction solar cell with 0.2 indium composition is 2.78%, above an indium composition of 20%, the modeled heterojunction devices do not operate as solar cells.